Pneumocystis carinii pneumonia complicating low dose methotrexate treatment for psoriatic arthropathy. Issue 3 (March 1989) - Wallis, P J; Ryatt, K S; Constable, T J
Abstract : A case of Pneumocystis carinii pneumonia complicating low dose methotrexate treatment for psoriasis and psoriatic arthropathy is described. This potentially fatal event was probably precipitated by an interaction between methotrexate and concurrent non-steroidal anti-inflammatory drugs, resulting in serious potentiation of the effects of methotrexate.